Compressive effect of jute fiber corrugated lattice sandwich structure. (March 2020) - Li, Shuguang; Hu, Runsheng; Cheng, Jin; Hu, Yingcheng
A lattice sandwich structure mainly consisting of jute fiber and resin epoxy was prepared. Two configurations were established, and six out-of-plane compression experiments were conducted to identify the factors affecting the mechanical properties of the samples. The specific strength of the 2D corrugated lattice truss with the struts at 30° (I1 ) was 3 times stronger than that of the sample with sandwich struts at 45°. The specific strength of I1 was 3.9 times stronger than that of the Kagome structure prepared using Cu–2%Be. The cost performance with respect to the specific strength of the structure I1 was 161.7 times higher than that of the Kagome structure prepared using Cu–2%Be. Three failure modes were considered, and theoretical predictions were made separately. The failure modes in the experiment were mainly shear failure and shear buckling failure in sandwich struts.